Principles of a Modern Qur’an Interpretation: Muhammad Abduh’s Reformation on the Methodology Reform of Qur’an Interpretation - Alba, Cecep; Siregar, Qoriah A.; Haq, Sansan Ziaul (Universiti Sains Malaysia, 2016)
The Qur’an is the source of the Islam teachings which has an absolute nature, while the tafsir of Qur’an is relative in nature. The mufasirs (interpreters) interpret the Qur’an in accordance to their educational background and capacity of knowledge. As the result, there are books of tafsir (interpretation) which have a tendency in certain areas. Based on the paradigm, Muhammad Abduh argues that the interpretation of Quran needs to be updated so that the guidance of the Quran illuminates the life of mankind. The research purposes: 1. To prove whether it is true that Abduh’s renewal originates from the tafsir methodology? 2. To know how his reformation in understanding the Qur’an is. 3. To know what his method is based on. Research methods used are normative doctrinal and descriptive analysis, because this research is concerned with theoretic aspects i.e. the tafsir theories. This research shows that Muhammad Abduh’s reformation on the methodology of the Qur’an interpretation is essentially based on modern rationalism. He pursues this way in order to make the Qur’an as the guideline to meet the demands of modernity faced by Muslims. For doing so, this modern method should be based on several principles: 1) The Qur’an is the primary source of Islamic dogmas; 2) The Quran is absolute and universal; 3) Reason is the primary means to understand the Qur’an, so rationality becomes the measure of the truth; 4) Very selective in interpreting verses with prophetic tradition (Hadith); 5) the main function of the Qur’an is as the guidance for mankinds.